The final stadium larva of Euphaea decorata Hagen in Selys, 1853, from Fujian, China (Odonata: Zygoptera: Euphaeidae) - Xu, Qi-Han (Zootaxa, 2017)
The final stadium larva of Euphaea decorata Hagen in Selys is described and illustrated for the first time. The larva of E. decorata is typical of the genus and characterized by having a flat and long body with large saccoid caudal gills, seven pairs of lateral abdominal gills, two or three large and sharp spines in front of the ventral margin of the eyes, and tridentate palpal lobes of the prementum. The supposed larva of Rhipidolestes nectans is corrected to that of an unknown Euphaeidae. Known Euphaea larvae are shown to be generally very similar, but an old report suggests that the Indian species E. dispar and E. fraseri may show sufficient differences to restore them to the genus Indophaea.